USING EXPERT OPINION IN HEALTH TECHNOLOGY ASSESSMENT: A GUIDELINE REVIEW. (9th August 2016) - Hunger, Theresa; Schnell-Inderst, Petra; Sahakyan, Narine; Siebert, Uwe
Abstract : Objectives: External experts can be consulted at different stages of an HTA. When using vague information sources, it is particularly important to plan, analyze, and report the information processing in a standardized and transparent way. Our objective was to search and analyze recommendations regarding where and how to include expert data in HTA. Methods: We performed a systematic database search and screened the Internet pages of seventy-seven HTA organizations for guidelines, recommendations, and methods papers that address the inclusion of experts in HTA. Relevant documents were downloaded, and information was extracted in a standard form. Results were merged in tables and narrative evidence synthesis. Results: From twenty-two HTA organizations, we included forty-two documents that consider the use of expert opinion in HTA. Nearly all documents mention experts in the step of preparation of the evidence report. Six documents address their role for priority setting of topics, fifteen for scoping, twelve for the appraisal of evidence and results, another twelve documents mention experts when considering the dissemination of HTA results. During the assessment step, experts are most often asked to amend the literature search or to provide expertise for special data analyses. Another issue for external experts is to appraise the HTA results and refer them back to a clinical and social context. Little is reported on methods of expert elicitation when their input substitutes study data. Conclusions: Despite existing recommendations on the use of expert opinion in HTA, common standards for elicitation are scarce in HTA guidelines.